2014
DOI: 10.1007/s12288-014-0380-6
|View full text |Cite
|
Sign up to set email alerts
|

Novel Βeta (β)-Thalassemia Mutation in Turkish Children

Abstract: Beta (b)-thalassemia is the most frequently observed hereditary blood disorder in the world. It is characterized by deficiency of hemoglobin b-globin gene and is also a profoundly heterogeneous both at the molecular and clinical level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
(34 reference statements)
1
1
0
Order By: Relevance
“…The second most common mutation was IVS-I-1 (G>A) with a frequency of 12.4% and the third most common was IVS-I-6 (T>C) with a frequency of 9.4%. The mutation profile in Turkish patients in our city is similar to the profile found out in the neighboring province Gaziantep [15].…”
Section: Discussionsupporting
confidence: 84%
“…The second most common mutation was IVS-I-1 (G>A) with a frequency of 12.4% and the third most common was IVS-I-6 (T>C) with a frequency of 9.4%. The mutation profile in Turkish patients in our city is similar to the profile found out in the neighboring province Gaziantep [15].…”
Section: Discussionsupporting
confidence: 84%
“…Codon 14 [+T] was specific for the Azerbaijanian population and has not been reported from other populations so far (Aliyeva et al., ). Codons 82/83 [–G], although first reported from Azerbaijan, were then identified in Czechs, Iraqi Kurds, Iranians, and Turks (Al‐Allawi, Jalal, Mohammad, Omer, & Markous, ; Indrak et al., ; Neishabury et al., ; Schwartz et al., ; Ulasli et al., ). Unlike previous studies, our study group solely consisted of β‐thalassemia carriers identified through population screening.…”
Section: Resultsmentioning
confidence: 99%